Impact of the first surge of the COVID‐19 pandemic on a tertiary referral centre for kidney cancer. (25th May 2021) - Kuusk, Teele; Cullen, David; Neves, Joana Briosa; Campain, Nicholas; Barod, Ravi; Boleti, Ekaterini; El‐Sheihk, Soha; Grant, Lee; Kelly, John; Marchetti, Marta; Mumtaz, Faiz; Patki, Prasad; et al.
Abstract : Objective: To analyse the impact of the COVID‐19 pandemic on a centralized specialist kidney cancer care pathway. Materials and Methods: We conducted a retrospective analysis of patient and pathway characteristics including prioritization strategies at the Specialist Centre for Kidney Cancer located at the Royal Free London NHS Foundation Trust (RFH) before and during the surge of COVID‐19. Results: On 18 March 2020 all elective surgery was halted at RFH to redeploy resources and staff for the COVID‐19 surge. Prioritizing of patients according to European Association of Urology guidance was introduced. Clinics and the specialist multidisciplinary team (SMDT) meetings were maintained with physical distancing, kidney surgery was moved to a COVID‐protected site, and infection prevention measurements were enforced. During the 7 weeks of lockdown (23 March to 10 May 2020), 234 cases were discussed at the SMDT meetings, 53% compared to the 446 cases discussed in the 7 weeks pre‐lockdown. The reduction in referrals was more pronounced for small and asymptomatic renal masses. Of 62 low‐priority cancer patients, 27 (43.5%) were deferred. Only one (4%) COVID‐19 infection occurred postoperatively, and the patient made a full recovery. No increase in clinical or pathological upstaging could be detected in patients who underwent deferred surgery compared to pre‐COVID practice. Conclusion: The first surge of the COVID‐19 pandemic severely impacted diagnosis, referral and treatment of kidney cancer at a tertiary referral centre. With a policy of prioritization and COVID‐protected pathways, capacity for time‐sensitive oncological interventions was maintained and no immediate clinical harm was observed.